Immunomodulation in Administration of rAAV: Preclinical and Clinical Adjuvant Pharmacotherapies - Chu, Wing Sum; Ng, Joanne (Frontiers in Immunology, 2021)
Recombinant adeno-associated virus (rAAV) has attracted a significant research focus for delivering genetic therapies to target cells. This non-enveloped virus has been trialled in many clinical-stage therapeutic strategies but important obstacle in clinical translation is the activation of both innate and adaptive immune response to the protein capsid, vector genome and transgene product. In addition, the normal population has pre-existing neutralizing antibodies against wild-type AAV, and cross-reactivity is observed between different rAAV serotypes. While extent of response can be influenced by dosing, administration route and target organ(s), these pose concerns over reduction or complete loss of efficacy, options for re-administration, and other unwanted immunological sequalae such as local tissue damage. To reduce said immunological risks, patients are excluded if they harbor anti-AAV antibodies or have received gene therapy previously. Studies have incorporated immunomodulating or suppressive regimens to block cellular and humoral immune responses such as systemic corticosteroids pre- and post-administration of Luxturna® and Zolgensma®, the two rAAV products with licensed regulatory approval in Europe and the United States. In this review, we will introduce the current pharmacological strategies to immunosuppress or immunomodulate the host immune response to rAAV gene therapy.